OUTCOME OF 0.2% GLYCERYLTRINITRATE CREAM VERSUS 2% DILTIAZEM CREAM IN THE TREATMENT OF CHRONIC ANAL FISSURE - Khan, Muhammad Siddique; Abar, Ismail; Zeb, Juniad; Ahmad, Salman; Khan, Ajmal (Journal of Ayub Medical College Abbottabad, 2017)
Background: Anal fissure is a linear tear in the distal anal canal resulting from persistent hypertonia and spasm of the internal sphincter which results in mucosal ischemia. We have conducted a study in order to compare the outcome of 0.2% glyceryl trinitrate cream versus 2% diltiazem cream in the treatment of chronic anal fissure Methods: This randomized controlled trial (RCT) was carried out in the Department of Surgical B unit, at Ayub Teaching Hospital, Abbottabad, Pakistan from 15th June 2012 to 15th May 2015. One hundred and eighty-four patients who visited the outpatient department for the treatment of chronic anal fissure were included in the study. They were divided into two groups with 92 patients in each group. Patients in group A included those patients receiving topical glyceryl trinitrate and group B patients were those receiving topical diltiazem cream. Results: Out of 184 patients 66.3% were males, 33.7% were females. Mean age of the patients was 43.84±7.976 and mean duration of symptoms was 10.55±2.524. Overall outcome in terms of healing was 71.2%, among which 80.4% were from diltiazem group while 62% in glyceryl trinitrate group. Complete relief of pain was observed in 67.9%, 26.1% complained of mild pain and 5.4% complained of moderate pain. Only one patient in glyceryl trinitrate group complained with severe pain with no healing after one month of follow up. No statistical association was found between healing outcome and gender as well as age of the patients (p>0.05) although an association was found between healing outcome and duration of symptoms (p<0.05). Conclusion: This study shows that diltiazem has better outcome in terms of healing of chronic anal fissure and reductions in symptoms, i.e., pain compared with glyceryl trinitrate. Keywords: Chronic anal fissure; Diltiazem; glyceryl trinitrate; cream; chemical sphincterotomy